Morphological and Morphometrical Studies on the Sternum of Chinese Goose (Anser cygnoides) - Sathyamoorthy, O. R.; Chruchil, R. Richard; Sangilimadan, K.; Dhamotharan, S. (International Journal of Livestock Research, 2020)
The sternum of Anser cygnoides consisted of a manubrium sterni, a corpus sterni and a sternal crest. The manubrium sterni is very small, flat and extended only from the middle of the ventral lip of the cranial border. The corpus sterni is large, quadrilateral, broad in the cranial two thirds and narrow in the caudal one third. The dorsal surface showed numerous pneumatic foraminae. An elongated deep transverse articular groove is seen in cranial border. The craniolateral processes are thin, short and broad. Seven articular cylinders and the troughs between them containing large pneumatic foraminae are seen at the lateral borders. The processes thoracicus was absent. The caudolateral processes extended beyond the caudal border of the sternum and enclosed along with the lateral border of the corpus sterni, the incisura ovalis. The sternal crest was prominent, projected from below the sternal spine, and ended before the caudal border.